Surface Chemical Studies on Galena and Sphalerite Using Mineral-Adapted Bacillus Polymyxa - D. Santhiya; S. Subramanian; K. A. Natarajan; S. S. Indi (International Mineral Processing Congress, 2003)
"With the gradual depletion of the high-grade ores and finer dissemination of values in the leaner samples, it has become imperative to develop innovative approaches to process such complex ores. The beneficiation of complex sulphide ores containing copper, lead and zinc minerals, remains one of the most important challenges in base metals metallurgy. The advent of biotechnology in mineral processing has opened up immense possibilities to exploit such difficult-to-treat ores. Bioprocessing techniques thus hold promise as potential substitutes for the conventional technologies in vogue. Several types of autotrophic and heterotrophic bacteria, fungi, algae and yeasts are implicated in mineral beneficiation processes. Adopting a bioprocessing route to mineral beneficiation has attractive benefits, such as lower cost and energy requirements, environmental acceptability and operational flexibility.The interaction of sphalerite- and galena-adapted Bacillus polymyxa (B. polymyxa) cells with sphalerite and galena has been investigated through adsorption, electrokinetic and flotation studies. The amount of sphalerite-adapted cells adsorbed onto sphalerite and galena is found to decrease with increase in pH. On the other hand, the adsorption density of galena-adapted cells onto galena shows a feeble maximum around pH 8, and the amount adsorbed is marginally higher in the pH range of 8 – 11.5. In the case of sphalerite the amount adsorbed is higher in the pH range of 5 to 7. The adsorption density of both the adapted cells is higher for galena vis-à-vis sphalerite. Electrokinetic studies indicate significant surface chemical changes on the chosen sulphide minerals and the bacterial cells, consequent to microbemineral interactions. Selective flotation tests on a synthetic mixture of galena and sphalerite confirm that sphalerite could be preferentially floated from galena, using galena-adapted cells, but not with the sphalerite-adapted cells. The cells adapted to galena assay a higher polysaccharide content and are more hydrophilic, while the sphalerite-adapted cells have a higher protein content and possess greater hydrophobicity. Transmission electron microscopic studies have provided evidence in support of the differences between the cell surface characteristics of sphalerite- and galenaadapted cells (Figure 1). Possible mechanisms of interaction between the minerals and the bacterial cells are discussed."